The chinese business in the rural area : a case study of Ng Wak Bazaar - Wong, Rosalind (Universiti Malaysia Sarawak, (UNIMAS), 2001)
The chinese presence in the interior land of Sarawak is a common phenomenon. Chinese trade with the local indigenous people has been established since the colonial times or even before then.Chinese presence in the rural area had changed the landscape and the land use. Besides taht, the Chinese trades have introduced a credit system, which basically supported the local cropping. The mutual dependence between chinese and the iban has made rural business succesful